Unveiling Inflammation: Blood Peripheral Indices in Pulmonary Tuberculosis - Gabriella M.C. Sipahutar; Jenny Ria Sihombing; Hendra Jirwanto; Nathalia E.R. Sipahutar; Suhartomi Suhartomi; Sadarita Sitepu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Pulmonary tuberculosis (TB) remains a global and national health challenge. Peripheral blood inflammatory indices—NLR, PLR, PNR, MLR, dNLR, SIRI, SII, and AISI—have been proposed as markers of systemic inflammation and prognosis, yet local data are scarce and findings vary. Thus, this study was aimed to describe these indices in pulmonary TB patients at Dr. Pirngadi Regional General Hospital, Medan (2019–2020). This cross-sectional study was analysed 105 inpatient medical record via total sampling technique. Demographics and eight inflammatory indices were analyzed using descriptive statistics. Median values ​​of NLR, PLR, PNR, MLR, dNLR, SIRI, SII, and AISI in pulmonary tuberculosis patients are quite varied and tend to be higher than several previous studies. High NLR and PLR values ​​can reflect a severe degree of inflammation, while PNR and dNLR values ​​show less consistent results. Indices such as SIRI, SII, and AISI show potential as indicators of systemic inflammation, but still require further study. These indices have the potential to be used as markers of inflammation and prognosis in pulmonary tuberculosis, but cannot yet be used as a single reference